Periodismo educativo como herramienta comunicacional en los estudiantes de tercero de bachillerato de la Unidad Educativa Dr. José María Velasco Ibarra en el cantón de Buena Fe, año 2019 - Guerrero Bravo, Johana Lisbeth (2020)
Currently the José María Velasco Ibarra Educational Unit is one of the largest institutions of Good Faith with a large number of students where the use of a digital newspaper will be very useful being a tool of great benefit creating and strengthening the communication system. The educational newspaper will be a model of teaching and learning where the contents attractive, interesting and close to the reality of the student will be acquired. It will be a connection between the digital medium and the student giving an efficient and very favorable experience to solve the inconveniences that occur since it will be an educational expertise. The proposal of this research project will be to make pedagogicals and students engage in this new purpose as it is a fundamental idea giving them training to make the digital newspaper a success inside and outside the College being the communication an essential basis to contribute in life.